Social Mobile Marketing: Evolution of Communication Strategies in the Web 2.0 Era - Franco, Stefano (TeMA - Journal of Land Use, Mobility and Environment, 2014)
Increasingly faster communicational streams - that ease interactions and allow agents to considerably enhance their own informational assets - characterize the era in which we live. The research about new media, mobile and social technologies is the driver of this changes that implements a revolution of the content management, of the information accessibility and of the relationships interactivity. These characteristics don’t leave the agents unresponsive and it is interesting and fitting to understand the tools available to firms and institutions and the communicational and marketing policies that organizations put to use to achieve their goals. In this context we want to find strategic and operational models to support organizations decisions about markets and territories. The purpose of this article is to understand how small organizations can utilize networks that characterize new trends in marketing. We conclude by providing some thoughts on the future evolution of the research in this field also with reference to the smart city that can exploit social mobile marketing for promotion of the territory and social participation. I